2019
DOI: 10.1007/s00300-019-02549-6
|View full text |Cite
|
Sign up to set email alerts
|

Polar cod egg and larval drift patterns in the Svalbard archipelago

Abstract: Spawning of polar cod (Boreogadus saida) in the vicinity of the Svalbard archipelago has not been directly observed. From the distribution pattern of polar cod 0-group observed during annual monitoring of the Barents Sea, it has, however, been inferred that spawning occurs in Svalbard waters most years. We wanted to investigate the possibility of back-tracking the larvae from these observed distribution areas to the spawning areas from which they originated and applied a coupled ocean-sea ice and particle trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…While the polar cod is found over large areas in the Barents Sea during the feeding season, spawning is apparently restricted to two separate regions; one in the Pechora Sea in the southeastern Barents Sea (Ponomarenko 1968) and one in the vicinity of Svalbard (Gjøsaeter 1973;Boitsov et al 2013). Recent particle drift studies, (Eriksen et al 2019;Huserbråten et al 2019) have corroborated the existence of two separate spawning areas in the region (Fig. 2).…”
Section: Short Description Of Studied Fish Stockmentioning
confidence: 62%
See 1 more Smart Citation
“…While the polar cod is found over large areas in the Barents Sea during the feeding season, spawning is apparently restricted to two separate regions; one in the Pechora Sea in the southeastern Barents Sea (Ponomarenko 1968) and one in the vicinity of Svalbard (Gjøsaeter 1973;Boitsov et al 2013). Recent particle drift studies, (Eriksen et al 2019;Huserbråten et al 2019) have corroborated the existence of two separate spawning areas in the region (Fig. 2).…”
Section: Short Description Of Studied Fish Stockmentioning
confidence: 62%
“…Our recent particle drift studies have shown that polar cod offspring observed in the northwestern Barents Sea could not come from the southeastern spawning areas (Huserbråten et al 2019). Furthermore, eggs spawned east of the Svalbard archipelago may drift clockwise around the archipelago and thus could end up in almost all the areas where polar cod juveniles have been observed around the archipelago (Eriksen et al 2019). This supports earlier findings of prespawners and polar cod juveniles around Svalbard (Ponomarenko 1968;Gjøsaeter 1973;Korshunova 2012;Boitsov et al 2013;Eriksen et al 2015).…”
Section: Discussionmentioning
confidence: 97%
“…The genetic population structure in the Northeast Atlantic remains unclear, as Nelson et al (2020) did not have samples from the Barents Sea. There is evidence of two distinct spawning populations in the southeastern Barents Sea (Pechora Sea) and in the northwestern Barents Sea east of Svalbard, respectively, supported by distinct distributions of eggs and larvae (Boitsov et al 2013) and by biophysical modeling studies (Huserbråten et al 2019;Eriksen et al 2020). Hypothesized spawning sites to the south, east, and north of the Svalbard Archipelago are consistent with the observed distribution of age-0 polar cod in the northwest Barents Sea (Eriksen et al 2020).…”
mentioning
confidence: 54%
“…There is evidence of two distinct spawning populations in the southeastern Barents Sea (Pechora Sea) and in the northwestern Barents Sea east of Svalbard, respectively, supported by distinct distributions of eggs and larvae (Boitsov et al 2013) and by biophysical modeling studies (Huserbråten et al 2019;Eriksen et al 2020). Hypothesized spawning sites to the south, east, and north of the Svalbard Archipelago are consistent with the observed distribution of age-0 polar cod in the northwest Barents Sea (Eriksen et al 2020). In contrast, particles released in the western fjords were largely retained in the fjords, consistent with previously reported fine-scale genetic structure differentiating fjord populations in western Svalbard and eastern Greenland from open ocean populations (Madsen et al 2016).…”
mentioning
confidence: 99%
“…With heightened activity comes increased risk of petroleum pollution 10 . Shipping routes (i.e., the Northern Sea Route and Northwest passage route) traverse important nursery grounds for Arctic fish species [11][12][13] .Early life stages (ELSs) of many fish face greater vulnerability to environmental stressors, owing to physical and biological factors 14,15 . To ensure survival and a strong year class, pelagic eggs and larvae must maintain their position in the water column through buoyancy control and swim bladder inflation, forage when yolk reserves are exhausted, grow quickly, and build up energy reserves for overwintering while avoiding predation 16 .…”
mentioning
confidence: 99%